2018
DOI: 10.1074/jbc.ra118.003862
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-451a in extracellular, blood-resident vesicles attenuates macrophage and dendritic cell responses to influenza whole-virus vaccine

Abstract: The authors declare that they have no conflicts of interest with the contents of this article. This article contains Figs. S1-S6 and Table S1. The microarray data were deposited to the Gene Expression Omnibus (GEO) database under GEO accession number GSE100128.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 64 publications
1
49
0
Order By: Relevance
“…Till date, several researches have demonstrated that miR-451a could inhibit the proliferation and differentiation of benign and malignant tumour cell and also affect the chemosensitivity of the tumour cells. Moreover, miR-451a in extracellular vesicles has been reported to influence the functions of immune cells, such as macrophages and dendritic cells [28,[33][34][35][36]. Hence, in the present study the predominantly enriched miR-451a in exosomes may be speculated to act as an important mediator in TRIM.…”
Section: Discussionmentioning
confidence: 48%
“…Till date, several researches have demonstrated that miR-451a could inhibit the proliferation and differentiation of benign and malignant tumour cell and also affect the chemosensitivity of the tumour cells. Moreover, miR-451a in extracellular vesicles has been reported to influence the functions of immune cells, such as macrophages and dendritic cells [28,[33][34][35][36]. Hence, in the present study the predominantly enriched miR-451a in exosomes may be speculated to act as an important mediator in TRIM.…”
Section: Discussionmentioning
confidence: 48%
“…Intriguingly, miR-195 has been implied in the pathophysiology of heart failure [39] and could play a role in the (dys)regulation of adrenergic-mediated responses, known to be critical in failing heart where they regulate both fibrosis and inflammation [40][41][42][43][44][45][46]: for instance, miR-195 has been reported to be upregulated by isoproterenol in the heart during catecholamine-induced hypertrophy [47]. Moreover, our findings pave the way for future investigation on the potential role of cardiosomal miRNAs in long-distance communications, since extracellular vesicles enriched in miRNAs have been recently found in blood [48,49]. Indeed, cells need to communicate efficiently with each other in order to propagate signals and coordinate functions [22].…”
Section: Discussionmentioning
confidence: 54%
“…Targeting EV production can therefore be a potential strategy of improving MRC-5 cell-based rabies vaccine production. Additionally, miRNAs in EVs affect the response to the influenza whole-virus vaccine (WV) (Okamoto et al, 2018). miR-451a is abundant in human serum EVs and its presence in blood-circulating EVs can attenuate the innate immune response of macrophages and dendritic cells to the inactivated influenza WV.…”
Section: Evs As a Negative Factor In Vaccine Productionmentioning
confidence: 99%